2018
DOI: 10.1371/journal.pone.0202017
|View full text |Cite
|
Sign up to set email alerts
|

Can the antral follicular count modulate the gene expression of bovine oviducts in Aberdeen Angus and Nelore heifers?

Abstract: The number of visible ovarian antral follicles (antral follicle count—AFC) is repeatable in bovine individuals, but highly variable between animals, and with differences between Bos taurus and Bos indicus breeds. Several studies have tried to determine the correlation between AFC and increased fertility in cattle. While the impacts of AFC on embryo production, hormonal levels, and pregnancy rates have been described, the molecular effects of AFC on bovine oviducts have not yet been investigated. Here, the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 83 publications
3
6
0
Order By: Relevance
“…Differences in responses between urban and rural settings, as well as by educational level, suggest that different intervention approaches should be developed to target specific segments of society. This conclusion is consistent with findings from previous community surveys on AMR in China and elsewhere [ 18 21 ]. Routine online surveys such as ours provide a low-cost and reproducible approach to monitor and evaluate changes in antibiotic use and public knowledge and awareness over time.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Differences in responses between urban and rural settings, as well as by educational level, suggest that different intervention approaches should be developed to target specific segments of society. This conclusion is consistent with findings from previous community surveys on AMR in China and elsewhere [ 18 21 ]. Routine online surveys such as ours provide a low-cost and reproducible approach to monitor and evaluate changes in antibiotic use and public knowledge and awareness over time.…”
Section: Discussionsupporting
confidence: 93%
“…In our survey, for example, a larger percent of respondents 16 to 24 years of age (49%) and of those with a high school education or less (38%) reported that antibiotics could be used to treat viral infections compared to the other demographic groups. National surveys on AMR in Japan [ 18 ] and Thailand [ 26 ] reported similar findings. Developing and disseminating education material on the role of antibiotics targeting these specific age- and education-level groups is likely to help address these knowledge gaps.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In line with this, the fact that three out of the four embryos recovered at Day 2.5 were at the 2‐cell stage—that is before major embryo genome activation, which in cattle occurs around the 8‐cell stage (Graf et al, )—could have influenced the oviduct response, which in vitro has been demonstrated to be embryo stage‐specific (Hamdi et al, ). Furthermore, comparison of the oviduct section containing the embryo and the corresponding contralateral section could be potentially misleading based on results describing an effect of the CL proximity (i.e., differences between the ipsilateral and contralateral oviducts) on the oviduct transcriptome in cyclic heifers at Day 1 (Fontes et al, ), 3 (Locatelli et al, ) or 3.5 after oestrus (Bauersachs et al, ). Use of technologies such as RNA sequencing may be more convenient in order to have a wider view of the embryo effect on oviduct gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (Bauersachs et al, 2004;Buhi, 2002;Buhi, Alvarez, & Kouba, 2000;Carrasco, Coy, Avilés, Gadea, & Romar, 2008;Fontes et al, 2018;Lamy, Labas, et al, 2016) have reported that OVGP1, HSPA5, FUCA1, and FUCA2 levels are stimulated by E2 during the periovulatory period. In our study, the increased levels of E2 resulted in the upregulation of OVGP1, HSPA5, FUCA1, and FUCA2 in the infundibulum and ampulla of the cows submitted to the FSH/eCG protocol relative to the control animals, and no effect of the treatments was observed in the isthmus.…”
mentioning
confidence: 99%